2021
DOI: 10.1017/s143192762100009x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Star Defects in Gallium Nitride with HREBSD and ECCI

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Use of GaN substrates manufactured with halide-vapor phase epitaxy (HVPE) reduces these defects but can introduce different defects. This study investigates one such defect, the star defect, recently reported in the literature [1]. These defects are hundreds of microns in size and may be related to defects reported in GaN substrates [2].…”
mentioning
confidence: 94%
“…Use of GaN substrates manufactured with halide-vapor phase epitaxy (HVPE) reduces these defects but can introduce different defects. This study investigates one such defect, the star defect, recently reported in the literature [1]. These defects are hundreds of microns in size and may be related to defects reported in GaN substrates [2].…”
mentioning
confidence: 94%
“…36 The technique has previously been successfully used to investigate the defect structure in solar cells, metals, and (0001) (c-plane) GaN. 34,[37][38][39][40] The first research on semi-polar GaN, investigating the widely used (11 22) orientation, was published by Naresh-Kumar et al 41 They demonstrated the ability of ECCI on semi-polar samples to locate threading dislocation clustering as well as identify the presence of BSFs.…”
Section: Introductionmentioning
confidence: 99%
“…EBSD patterns were obtained using an EDAX Clarity TM direct electron detector at 512 x 512 pixel resolution. HR-EBSD calculations were performed using OpenXY [5]. Figure 1 shows one of the shear components of the elastic strain gradient tensor for the sample investigated.…”
mentioning
confidence: 99%
“…Such an analysis has been applied to the AM stainless steel sample as shown in Figure 2 where the color at each point correspond to the polar coordinates of Burgers and line vectors. From these measurements, the Burgers vector for the each of three notable structures was found to vary from [110] at the left, [1][2][3][4][5][6][7][8][9][10] for the center and a mixed at right. These results demonstrate the ability to rapidly characterize dislocation structures in terms of defect character, distribution, and associated strain fields, opening up the possibility of high throughput defect structure characterization in AM parts.…”
mentioning
confidence: 99%